Penyuluhan Pencegahan Pernikahan Dini Pada Remaja Melalui Layanan Psikologi Latar Komunitas: Studi Pada Forum Anak Desa G - Dimas Suprayoga Sampudeq; Sayidah Aulia'ul Haque (Universitas Muhammadiyah Gresik, 2026)
Background: Early marriage remains a social problem influenced by community norms, family pressure, and low psychological readiness of adolescents. Objective: This study aims to describe the role of community-based psychological services in preventing early marriage among adolescents through the Village G Children's Forum. Method: The study used a descriptive qualitative approach with adolescents aged 12–17 years who are members of the Children's Forum as subjects. Data were collected through observation, interviews, Focus Group Discussions (FGDs), and qualitative psychoeducational assessments. Analysis was conducted using thematic analysis with data triangulation. The results showed that before the intervention, early marriage was perceived as a normal practice, accompanied by low future orientation and adolescent self-efficacy. Result: After the intervention, adolescents showed increased awareness of the psychological impacts of early marriage and the importance of psychological readiness in life decision-making. Conclusion: This study concludes that community-based psychological services through the Children's Forum play an effective early preventive role in increasing adolescents' awareness and critical reflection on early marriage.